Mitigation of drought stress effect on growth and productivity of mung bean by foliar application of sorghum water extract - Al-Hussaini, Muna; Alsaadawi, Ibrahim (Iraqi Journal of Science, 2023)
Field trial was conducted in Research Field equipped with rainfall transparentshade, Biology Department, College of Science, Baghdad University during thegrowing season of 2012 to test the potential of sorghum water extract in improvingyield and yield components of local cultivar of mung bean crop grown underdifferent moisture deficit stresses. The water stresses were applied by irrigated theplots to field capacity and withheld the next irrigation until the soil water deficitreaches 80, 50 and 30% of field capacity for control, mild water stress and higherwater stress, respectively. Foliar application of sorghum water extract at 0 ( control),2.5 and 5% (W/V) was made at preflowering, flowering and fruiting stages. Theexperiment was conducted in split plot design with four replications for eachtreatment. The sorghum water extract rates were kept in the sub plot while moisturedeficits were assigned as main plot.Results showed that drought stress significantly reduced the averages seedyield , dry matter accumulation, number of pods per plant, number of seeds per podand plant height. Foliar applications of sorghum extracts significantly increasedseeds yield, dry weight biomass, number of seeds per pod and plant height. Theinteraction of drought stress and sorghum water extract treatment significantlyaffected seed yield , dry matter accumulation, number of pods per plant, totalchlorophyll content and plant height. Application of sorghum water extract undersevere moisture deficit stress (i.e., 70% field capacity) increased seed yield, dryweight biomass and plant height , number of pods per plant, number of seeds perpod by 37.8%, 48.9%,64.3%,8.7% and 5.1%, of control, respectively compared thereduction achieved by the sever moisture deficit applied alone which was 58.50% ,56.06% , 57.17% , 48.05% and 14.78 % of control for the aforementionedparameters respectively.Chlorophyll content was found to be increased by effected by application ofsorghum extracts at control moisture treatment. Proline content of leaves wassignificantly increased by high drought stress when water extract applied alone.However, such differences disappeared when sorghum extract was applied,suggesting another mechanisms could be responsible for the stimulatory effect ofsorghum extract under drought stress.